Quantum Chemical Descriptor Based QSAR Study on β-Carbolines Binding to Benzodiazepine Receptor - Kumar Soni, Anil; Kumar Sahu, Vishnu; Prasad Singh, Pashupati (Asian Journal of Chemistry, 2010)
QSAR study of derivatives of β-carboline has been made with the help of quantum chemical descriptors. For QSAR study, the molecular modeling and geometry optimization for all the derivatives were carried out with CAChe Pro software using PM3 methods. QSAR model, "RE23 = -0.0141829*ΔHf 0 + 0.0428252* MW + 0.150185* ET -1.42607*εLUMO + 5.56043" can be useful for predicting the activity of new β-carbolines prior to their synthesis. ΔHf0, MW, ET and εLUMO are reliable descriptor for predicting activity. QSAR model indicates that these descriptors have significant relationships with observed bioactivity.